Bridging Clinical Practice and Research in a Teaching Hospital Setting - Khan, M Nuruzzaman (Journal of Shaheed Suhrawardy Medical College, 2025)
Abstract not available J Shaheed Suhrawardy Med Coll 2024; 16(1): 1-1